ICNP ® nursing diagnoses, outcomes and interventions for community elderly - Jorge Wilker Bezerra Clares; Maria Miriam Lima da Nóbrega; Maria Vilaní Cavalcante Guedes; Lúcia de Fátima da Silva; Maria Célia de Freitas
ABSTRACT Objective: To construct a nomenclature of nursing diagnoses, outcomes and interventions for elderly people under follow-up in the Family Health Strategy by using the International Classification for Nursing Practice and the theoretical reference of Virginia Henderson. Method: Methodological study developed according to guidelines of the International Council of Nurses. Results: A total of 127 concepts of nursing diagnoses/outcomes were constructed and distributed according to nursing care components in the subcategories of Biological/Physiological, Psychological, Social and Spiritual/Moral components. For these diagnoses, were proposed 551 nursing interventions. Conclusion: The concepts constructed may favor integral care for the elderly in the Family Health Strategy and the structuring of a terminological subset for this clientele.